Interpretation Criteria for Comparative Intradermal Tuberculin Test for Diagnosis of Bovine Tuberculosis in Cattle in Maroua Area of Cameroon - J. Awah-Ndukum; J. Temwa; V. Ngu Ngwa; M. M. Mouiche; D. Iyawa; P. A. Zoli (Veterinary Medicine International)
Intradermal tuberculin test (TST) is the choice method for diagnosis of bovine tuberculosis (Tb) in live animals. This work was done to assess the performance of single intradermal comparative cervical tuberculin (SICCT) test in randomly selected cattle in Maroua, Cameroon, against detection of Tb lesions and detection of Tb lesions plus acid fast bacilli in lesions. While 22.28% of slaughtered cattle presented Tb lesions at meat inspection, detection rates of anti-bovine-Tb antibody, Tb lesions, and Tb lesions plus acid fast bacilli were 68.57%, 32.95%, and 22.35%, respectively. SICCT-bovine-Tb positive cattle were 35.29%, 29.41%, 25.88%, 24.7%, and 21.18% at ≥2 mm, ≥2.5 mm, ≥3 mm, ≥3.5 mm, and ≥4 mm cut-offs, respectively. Higher sensitivity and predictive values were obtained at severe interpretations. The best performance was at ≥3 mm and ≥3.5 mm cut-offs. Against detection of Tb lesions, ≥3 mm and ≥3.5 mm showed sensitivity of 67.8% and specificity of 94.7% and 96.5%, respectively. For detection of Tb lesions accompanied with acid fast bacilli in lesions, ≥3 mm and ≥3.5 mm showed sensitivity of 89.4% and specificity of 92.4% and 93.9%, respectively. These findings revealed that interpretations of SICCT-bovine-Tb should be at ≥3 mm and/or ≥3.5 mm cut-offs. Severe interpretation of TST is essential for optimal diagnosis of bovine Tb in cattle in Maroua, Cameroon.